2018
DOI: 10.1111/tmi.13136
|View full text |Cite
|
Sign up to set email alerts
|

Excessive mortality and loss to follow‐up among HIV‐infected children in Guinea‐Bissau, West Africa: a retrospective follow‐up study

Abstract: This study reveals a high rate of early mortality and loss to follow-up among HIV-infected children in Guinea-Bissau. Initiatives to improve patient retention are urgently needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…This study found an increase in the number of infants not receiving PMTCT. An increase in the number of HIV-infected children and high rates of HIV infection (9.3%) despite PMTCT have been reported in Guinea-Bissau, suggesting poor treatment retention and challenges to PMTCT coverage and follow-up 15 . While an increase in the number of HIV-infected children may be due to better diagnostics, the late diagnosis of children (median age 3.5 years) suggests a large proportion of children die before being diagnosed with HIV 15 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This study found an increase in the number of infants not receiving PMTCT. An increase in the number of HIV-infected children and high rates of HIV infection (9.3%) despite PMTCT have been reported in Guinea-Bissau, suggesting poor treatment retention and challenges to PMTCT coverage and follow-up 15 . While an increase in the number of HIV-infected children may be due to better diagnostics, the late diagnosis of children (median age 3.5 years) suggests a large proportion of children die before being diagnosed with HIV 15 .…”
Section: Discussionmentioning
confidence: 99%
“…High rates of early mortality and loss to follow-up have recently been described among HIV-infected children (< 15 years of age) in Guinea-Bissau. Based on a study of 525 HIV-infected children, 11% died and 39% were lost to follow-up within the first year of follow-up, highlighting continuous challenges with implementing sustainable PMTCT services 15 . Consequently, there remains a paucity of research exploring the delivery of PMTCT services with the overall aim of improving treatment and care for HIV-infected mothers and their children in Guinea Bissau.…”
Section: Introductionmentioning
confidence: 99%
“…The mortality rate in our cohort is comparable to multiyear mortality results in other low resource settings with similar HIV disease burden. A recent national study in Togo found mortality rate of 4.5 per 100 person-years for children ages 0-15 at 8 years (Mouhari-Touré et al, 2018) while a 10-year study of children in Guinea-Bissau found 10.4 per 100 personyears (Steiniche et al, 2018). A longitudinal analysis of 8 years in 2017 found 10.1 per 100 person-years in Bali, Indonesia (Utami et al, 2017).…”
Section: Comparability To Previous Studiesmentioning
confidence: 99%
“…One of the fundamental reasons for the high LTFU rate is that we still lack a suitable predictive model for LTFU [11]. Hence, we cannot take effective measures before the occurrence of LTFU to prevent it [5,[7][8][9][10][11][13][14][15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%